CONTROL AND SUPERVISION OVER THE IMPLEMENTATION OF MEASURES FOR INTERCEPTION OF COMMUNICATIONS - THE MACEDONIAN CASE - Ilijevski, Ice; Krstevska Savovska, Katerina (NBP. Nauka, bezbednost, policija, 2021)
e implementation of the measures for interception of communications is a useful tool in ghting organized crime and endangering public and national security. However, if they are not in accordance with the law, their implementation can seriously jeopardize the privacy of individuals. In the past, there had been several Macedonian a airs related to the illegal surveillance of communication that caused reformation of the system for interception of communications. erefore, if certain inconsistencies are timely detected and signalized by the representatives of the control and supervising bodies, then there should be an adequate reaction for protection of the general values of the democratic society. Having in mind the above, the paper will give an overview of the current Macedonian situation regarding the system of control and supervision of the measures for interception of communications, or to be more precise - it will analyse the institutions and bodies that have authority to control and supervise. A special emphasis will be given to the de ciencies and weaknesses of this system, as well as the necessity for its upgrading and improving in order to prevent possible abuses in the future.